Exploration of Field Independent Students’ Mathematical Problem-Solving Ability in Ordinary Differential Equations Learning - Rezi Ariawan; Suhandri Suhandri; Norazman Norazman (Juring (Journal for Research in Mathematics Learning), 2025)
This study aims to analyze and describe students' mathematical problem-solving abilities in an ordinary differential equations course, using cognitive styles as a framework. This study is qualitative and uses a case study approach. The subjects were students of the Mathematics Education study program at the Faculty of Teacher Training and Education, Riau Islamic University. The selection of research subjects for in-depth interviews was conducted using purposive sampling. The instruments used were mathematical problem-solving ability tests, GEFT tests, and interview sheets that had met the eligibility criteria. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed that field independent subjects had a strong foundation in solving ordinary differential equations problems, especially in the initial analysis and application of procedures. However, weaknesses remained in evaluating data adequacy and in strategic reflection. Hence, the subjects were not fully able to adjust the length and depth of the solution to the demands of the problem.